2015
DOI: 10.1111/vco.12157
|View full text |Cite
|
Sign up to set email alerts
|

Masitinib monotherapy in canine epitheliotropic lymphoma

Abstract: This study evaluated efficacy and side effects of masitinib in canine epitheliotropic lymphoma. Complete remission occurred in 2 of 10 dogs and lasted for median 85 days. Five dogs went into partial remission for median 60.5 days. Three pretreated dogs did not respond to therapy. Side effects occurred in six dogs and were mostly mild to moderate. Immunohistochemistry was available for eight dogs. KIT receptor was negative in all of them, six of eight lymphomas stained strongly positive for stem cell factor (SC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
38
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 40 publications
1
38
0
Order By: Relevance
“…Epitheliotropic lymphoma (EL) is an uncommon form of lymphoma in dogs, representing 3–8% of canine lymphoma and <1% of canine cutaneous tumours . The aetiology for this malignancy in dogs is unknown .…”
Section: Introductionmentioning
confidence: 99%
“…Epitheliotropic lymphoma (EL) is an uncommon form of lymphoma in dogs, representing 3–8% of canine lymphoma and <1% of canine cutaneous tumours . The aetiology for this malignancy in dogs is unknown .…”
Section: Introductionmentioning
confidence: 99%
“…Other groups have demonstrated that TOC has high bioavailability and is usually well tolerated [ 16 ]. Masitinib, another TKI that targets PDGFR, VEGFR and KIT, also inhibits the growth of canine lymphoma cells in vitro [ 6 , 19 ]. Moreover, the same groups have reported that KIT is expressed at high levels in dogs with high-grade T-cell lymphomas, and that masitinib shows antitumor effects in these dogs [ 5 , 6 ].…”
mentioning
confidence: 99%
“…One study reported that the ORR to masitinib was 70% in canine epitheliotropic T-cell lymphoma. In the same study, the median PFI of the subjects that exhibited CRs was 85 days, and that of the subjects that exhibited PRs was 60.5 days [ 6 ]. In this clinical trial, it was suggested that TOC might be more effective against T-cell lymphoma than B-cell lymphoma.…”
mentioning
confidence: 99%
“…This finding is particularly interesting as PDGFRb is a target for therapies in canine mast cell tumors, 22 osteosarcoma, 15,35 and epitheliotropic lymphoma. 26 Furthermore, the application of a multitargeted tyrosine kinase receptor inhibitor has been demonstrated to reduce STS growth in a murine model by reducing both the proliferation of neoplastic cells and angiogenesis. 56 Therefore, these therapies might provide a further option for the treatment of STSs after marginal/incomplete resection, a circumstance leading to a high risk of recurrence 13 that is usually managed with radiation therapy.…”
Section: Discussionmentioning
confidence: 99%